Effects of hypoxia and reoxygenation on mitochondrial functions and transcriptional profiles of isolated brain and muscle porcine cells - Linda Adzigbli; Eugene P. Sokolov; Klaus Wimmers; Inna M. Sokolova; Siriluck Ponsuksili (Scientific Reports, 2022)
Abstract Oxygen fluctuations might occur in mammalian tissues under physiological (e.g. at high altitudes) or pathological (e.g. ischemia–reperfusion) conditions. Mitochondria are the key target and potential amplifiers of hypoxia-reoxygenation (H-R) stress. Understanding the mitochondrial responses to H-R stress is important for identifying adaptive mechanisms and potential therapeutic solutions for pathologies associated with oxygen fluctuations. We explored metabolic response to H-R stress in two tissue types (muscle and brain) with different degrees of hypoxia tolerance in a domestic pig Sus scrofa focusing on the cellular responses independent of the systemic regulatory mechanisms. Isolated cells from the skeletal muscle (masseter) and brain (thalamus) were exposed to acute short-term (15 min) hypoxia followed by reoxygenation. The mitochondrial oxygen consumption, reactive oxygen species (ROS) production rates and transcriptional profiles of hypoxia-responsive mRNA and miRNA were determined. Mitochondria of the porcine brain cells showed a decrease in the resting respiration and ATP synthesis capacity whereas the mitochondria from the muscle cells showed robust respiration and less susceptibility to H-R stress. ROS production was not affected by the short-term H-R stress in the brain or muscle cells. Transcriptionally, prolyl hydroxylase domain protein EGLN3 was upregulated during hypoxia and suppressed during reoxygenation in porcine muscle cells. The decline in EGLN3 mRNA during reoxygenation was accompanied by an upregulation of hypoxia-inducible factor subunit α (HIF1A) transcripts in the muscle cells. However, in the brain cells, HIF1A mRNA levels were suppressed during reoxygenation. Other functionally important transcripts and miRNAs involved in antioxidant response, apoptosis, inflammation, and substrate oxidation were also differentially expressed between the muscle and brain cells. Suppression of miRNA levels during acute intermittent hypoxia was stronger in the brain cells affecting ~ 55% of all studied miRNA transcripts than in the muscle cells (~ 25% of miRNA) signifying transcriptional derepression of the respective mRNA targets. Our study provides insights into the potential molecular and physiological mechanisms contributing to different hypoxia sensitivity of the studied tissues and can serve as a starting point to better understand the biological processes associated with hypoxia stress, e.g. during ischemia and reperfusion.